Challenges in Enforcing License Revocation for Companies Violating Employment Laws: Legal, Financial, and Operational Perspectives - Fauzi Zalmi; Ghandy Ghandy; Bobby Hidayat (IHSA Institute, 2025)
This research examines the challenges faced by regulatory bodies in enforcing license revocation for companies that violate employment laws. Despite the critical role of license revocation in ensuring compliance and protecting workers' rights, regulatory bodies often encounter significant barriers, including legal ambiguities, resource constraints, corporate resistance, political pressures, and complications arising from globalization. The primary objective of this study is to investigate these challenges and assess their impact on the effectiveness of license revocation enforcement. Using a qualitative approach, this research analyzes case studies, interviews with regulatory authorities, and a review of relevant legal frameworks. The findings reveal that unclear legal standards, insufficient resources, and external pressures significantly hinder enforcement efforts, allowing some companies to evade penalties. The study concludes that regulatory bodies need clearer legal frameworks, more resources, and stronger public support to enhance enforcement. This research contributes to a deeper understanding of the obstacles in labor law enforcement and offers insights for future policy improvements and cross-border regulatory collaboration.